Industry 4.0 in Brazil: challenges of the automotive segment for supply chain integration (Research, Society and Development, 2021)
Industry 4.0 offers opportunities for the evolution of production processes through the intensive use of new technologies which can transform the industrial sector, business models and skills to add value throughout the operations of the production chain. This article seeks to identify the challenges of the automotive segment in Brazil to integrate the supply chain, comparing the conditions that Autoparts and Automakers have for the adoption of 4.0 Industry technologies. Data were collected through a survey research applied to professionals in the automotive sector. The results indicated that Autoparts prioritize the permanence in the market, contrary to strategies to promove more investments to use new technologies, which automakers are at a more advanced stage, as they have greater investment capacity, access to new technologies and other necessary resources to transition.